Zipper-interacting protein kinase mediates neuronal cell death and cognitive dysfunction in traumatic brain injury via regulating DEDD - Yingxue Mei; Fei She; Ling Zhang; Gamin Kim; Ruomeng Li; Xiuzhi Zheng; Zonghai Wang; Renxuan Chen; Long Wang; Dongmei Chen; Jungho Kim; Tao Zhang; et al. (Cell Death and Disease)
Abstract Neuronal cell death is a causative process in traumatic brain injury (TBI)-induced structural and functional impairment of the central nervous system. However, the upstream trigger of TBI-induced neuronal loss and the underlying molecular pathways remain unclear. Zipper-interacting protein kinase (ZIPK) has been shown to be upregulated in Alzheimer’s disease and ischemic stroke and to play a role in cellular apoptosis, while its pathological significance in TBI has not been reported. Herein, we discovered for the first time that ZIPK expression was markedly elevated in neurons after TBI and that ZIPK caused massive neuronal apoptosis in peri-contusional brain regions. Zipk haploinsufficiency antagonized neuronal cell death and reversed several typical neuropathological changes induced by TBI. Mechanistically, we found that ZIPK affected neuronal viability by modulating death effector domain-containing DNA binding protein (DEDD) and caspase-3 pathway. Specifically, ZIPK could bind to and phosphorylate DEDD at the S9 residue, thus enhancing the stability of DEDD, and leading to the activation of caspase-3-mediated apoptotic cascade in neurons. The rescue of neuronal loss by ZIPK downregulation effectively alleviated TBI-induced behavioral deficits by preserving motor and cognitive abilities in vivo, supporting the decisive role of ZIPK dysregulation in TBI-associated neuronal dysfunctions by modulating neuronal survival. Furthermore, pharmacological suppression of ZIPK activity by a specific inhibitor prior to TBI protected neurons from brain injury-induced cell death and neuronal degeneration in vitro and in vivo by preventing DEDD upregulation and caspase-3 activation. In conclusion, our data reveal the essential contribution of ZIPK to TBI-induced neuronal cell death through the DEDD/caspase-3 cascade, and suggest the potential of targeting ZIPK as an effective strategy for treating TBI-related neuropathologies.